Numerical study of active mixing over a dynamic flow field in a T-jets mixer-Induction of resonance - Ertugrul Erkoç (2016)
The flow field in a 2D T-jets mixer was simulated to study the effect of the pulsation/modulation of the jets flow rate on the dynamics of mixing. Different strategies, frequencies and amplitudes of the opposed jets flow rate modulation were tested. The modulation frequencies were set as multiples of the natural oscillation frequencies of the dynamics flow field. The natural flow frequencies are determined from the unforced flow, i.e., when the jets are not modulated. It is found that out phase modulation of the opposed jets, with frequencies close to the natural frequencies, cause resonance of the flow enhancing the order of the system, which results in a flow field with a well-defined repetitive generation of vortices. Conversely, when the pulsation frequencies were different from the natural frequencies the flow disorder was enhanced, i.e., the vortices evolution throughout the T-jets mixers is less repetitive. The impact of the jets flow rate modulation on the flow field dynamics increases with the modulation amplitude up to the extreme case where it completely drives the dynamics of the system. A design equation for the most energy efficient pulsation of the jets feed streams in opposed jets mixers is proposed. (c) 2015 The Institution of Chemical Engineers.